БЕРЕЗА ПОВИСЛА (BETULA PENDULA ROTH) У ЛІСАХ ЛІВОБЕРЕЖНОГО ЛІСОСТЕПУ УКРАЇНИ - Meshkova, V.L.; Koshelyaeva, Y.V. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2018)
Introduction The area of silver birch (Betula pendula Roth) stands in the forest fund of the State Agency of Forest Resources of Ukraine amounts to 5.7 % from forest covered area, in the Forest Steppe zone it does not exceed 2 % of area. In the Left-bank Forest Steppe silver birch often participates in protective stands, forest shelter belts, in greening of cities, but rather rare in forest stands. However, the high ecological value of silver bitch is proved, particularly, its role in increase of resistance of mixed plantations to pests and diseases, particularly to pine bark bug, root rot, fire damage etc. Recently sanitary condition of silver birch has been worsened in many regions. To recover the causes of this phenomenon it is necessary to recognize, which forest site conditions and stands are typical for this tree species, and then to carry out detailed research in the permanent sample plots. The aim of this work was to recognize the peculiarities of silver birch spread in the stands of the Left-bank Forest Steppe by forest inventory data for State forest enterprises. Materials and Methods Forest inventory data for State enterprises of the State Agency of Forest Resources of Ukraine (by 1.01.2012) were analyzed for Chernigiv, Kyiv, Sumy, Poltava and Kharkiv regions. Database of Production Association "Ukrderzhlisproekt" was analyzed for the State Forest Enterprises which are located in the Left-bank Forest Steppe. Sumy region was represented by two State Enterprises: "Okhtyrske Forest Economy" (FE) and "Trostyanetske FE. Poltava region was also represented by two State Enterprises: "Gadyatske FE" and "Poltavske FE". Kharkiv region was represented by six State Enterprises: "Vovchanske FE", "Gutyanske FE", "Zmiivske FE", "Chuguevo-Babchanske FE", "Skrypaivske Training & Experimental Forest Economy" of Kharkov National Agrarian University named after V.V. Dokuchaev ("Skrypaivske TEFE"), and Kharkivska Forest Research Station of Ukrainian Research Institute of Forestry & Forest Melioration named after G.M. Vysotsky ("Kharkivska FRS"). The data were analyzed using MS Excel. Coordinates for forests of each forest enterprise were evaluated as centroids of respective contours of the territory using MapInfo Mapping Package. Results and Conclusions Area of birch stands in the forest fund of forest enterprises, which are totally located in the Left-bank Forest Steppe varies from 86.1 ha (State Enterprise "Chuguevo-Babchanske FE") to 554.3 ha (State Enterprise "Gadyatske FE"). Area and part of birch stands in the forest fund of analyzed enterprises decrease with longitude. The mean age of birch stands in analyzed Forest Enterprises of the Left-bank Forest Steppe varies from 31 to 50 years old; mean site class (bonitet) is 1A. Mean density of stocking and stock of birch stands tend to decrease from north to south. Birch stands in the forest fund of analyzed forest enterprises are represented in 32 forest types, mainly in the fresh and moist relatively poor conditions (subor), fresh and moist relatively fertile (sugrud) and fresh fertile (grud) site conditions. Obtained data must be used during investigations of sanitary condition of silver birch and the causes of its worsening.